Holistic Approach for Studying the Shadow Economy. The Case of Bulgaria - Chengelova, Emilia (Journal of Economic Sociology, 2016)
The shadow economy is one of the most provocative areas in current research. The present article summarizes the basic theoretical issues discussed by Bulgarian sociologists to measure and explain the shadow economy in one typical postsocialist country. The brief historical review provided here illustrates that 1) the shadow economy is the most appropriate construct for explaining activities done with violations of formal rules; 2) there are four basic categories of methodological approaches for studying the scope and forms of the shadow economy; and 3) if applied correctly and in compliance with methodological rules, sociology and social survey research is capable of generating reliable and scientifically sound knowledge about the shadow economy. The current article reveals a successful attempt to design and implement a holistic research methodology for studying the shadow economy through typical instruments of sociology. The methodological experience accumulated by one Bulgarian team (2010–2015) provides solid evidence that sociology and social survey research has rich epistemological and cognitive potential for collecting empirical data about the nature and specific functions of shadow practices, as well as the incentives that drive social actors to participate in shadow activities.